Ser-atriz e ser-professora – a busca pelo ser-perfeito: atravessamentos de uma trajetória na Graduação em Teatro - SILVA, Renata dos Santos (2019)
The present study revolves around the following question: “for to be a theater teacher, need to be an actress/actor?”. This questioning drives research and my professional training. The work exposes the paths I have taken, a student of Theater Graduation who wanted to be an actress, but saw herself in a course that would make her a theater teacher. I point out relevancies that go through and transform the research process. From the Greek myth of the soul mates, which I take as an analogy, I divide myself into two halves: the be-actress and the be-teacher, who sought to find to form the be-perfect. I base myself on my experiences, feelings, sensations and choices that I made, trying to answer the question. I do not want that my trajectory to be taken as the only way of solving the question. I want to provoke reflections, because the question exists so that each one analyzes it according to its practice. I have encounters with authors that bring light to my reports and analyzes about the process of construction my be-perfect, however, I choose to produce this research, primarily, from the authority that I have, and that only I have, to talk about my theatrical path and the discoveries of the actress and teacher that I am. I do not conclude saying "yes" or "no" to the questioning, because the only certainty I have is that nothing is finalized. Does this be-perfect really exist? I am in a state of searching, this "be" is under construction, I search what I lack, the be-perfect wants to reveal the search, the "be" is future.